Extract of Bombycis Feces suppressed 3T3-L1 adipogenesis resulting in the regulation of fatty acid-dependent energy consumption - Yun Kyung Lee; Ji Hyo Lyu; Ung Cheol Shin; Subramanian Muthamil; Chang-Hwan Bae; Seon-Wook Kim; Jong Min Oh; Hyun-Jun Jang; Jun Hong Park (Scientific Reports)
Abstract In Oriental medicine, silkworms and their derivatives have been used for anti-inflammatory and diabetic purposes. Bombycis Feces exhibit anti-atopic effects and anti-proliferative activity; however, the role of BF extract (BFE) in adipogenesis and obesity and management remains underexplored. This study examined the effects of BFE on amino acid oxidation during adipocyte differentiation. An adipogenesis model was established using 3T3-L1 cells. Intracellular lipid accumulation was assessed via Oil Red O staining, while cytotoxicity was evaluated using a cell viability assay. The effects of BFE on gene and protein expression, lipolysis, real-time oxygen consumption rate, and substrate oxidation during adipocyte differentiation were analyzed. The involvement of the branched-chain amino acid (BCAA) catabolic pathway and leptin gene expression was also evaluated. BFE treatment significantly downregulated the expression level of key adipogenic transcription factors, including PPARγ and C/EBPα, as well as aP2 gene expression. Lipid accumulation was significantly reduced, accompanied by increased expression of Sirt1 and Sirt6, but not Sirt3, and a concurrent reduction in Parp1 expression. In addition to adipogenesis, the oxygen consumption rate and extracellular acidification rate were downregulated by BFE treatment in adipocytes. Conversely, BFE enhanced amino acid-dependent oxidation during adipogenesis. These findings suggest that BFE supports energy production via BCAA catabolism rather than fatty acid or glucose oxidation. BFE inhibits adipogenesis by modulating the expression of Sirt1, Sirt6, and Parp1, reducing lipid metabolism, and enhancing BCAA catabolism in 3T3-L1 cells. These results highlight BFE’s potential as a therapeutic agent for obesity management.